2020
DOI: 10.1101/2020.06.25.096552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased axon initial segment length results in increased Na+currents in spinal motoneurones at symptom onset in the G127X SOD1 mouse model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis is a neurodegenerative disease preferentially affecting motoneurones. Transgenic mouse models have been used to investigate the role of abnormal motoneurone excitability in this disease. Whilst an increased excitability has repeatedly been demonstrated in vitro in neonatal and embryonic preparations from SOD1 mouse models, the results from the only studies to record in vivo from spinal motoneurones in adult SOD1 models have produced conflicting findings. Deficits in repetitive fir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 101 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Due to the slow breeding of our colony of the G127X, mice of both genders were used. Our previous controls have shown no effect of sex on AIS parameters in adult C57BL/6 J mice 37 . Figure 7.…”
Section: Scientific Reports |mentioning
confidence: 72%
See 1 more Smart Citation
“…Due to the slow breeding of our colony of the G127X, mice of both genders were used. Our previous controls have shown no effect of sex on AIS parameters in adult C57BL/6 J mice 37 . Figure 7.…”
Section: Scientific Reports |mentioning
confidence: 72%
“…We have previously observed from a larger sample of rat motoneurones that AIS width correlates with soma size, with larger motoneurones having wider AISs 37 . Furthermore, wider AISs were usually shorter and located more proximal to the somas.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, at symptom onset, the axon initial segment elongates and Na + currents appear to be increased in this region (Jørgensen et al . 2020). Conversely, studies using the G93A SOD1 and FUS models have reported a lack of repetitive firing in response to a triangular current ramp injection in the soma of some motoneurones, which has been interpreted as a hypo‐excitability of the motoneurones (Delestree et al .…”
Section: Introductionmentioning
confidence: 99%
“…This is highly relevant because excitability changes are observed with disease progression in the G127X SOD1 mouse (Jørgensen et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation